Strengthening Young Generation Character with Islamic Education from Preschool in 5.0 Society - Andi Irlina (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
The 5.0 industrial revolution era require people to have competence in using technology. People tend to use technology to run everyday activities, includes education. It lessen human role physically and facilitate them to achieve their goals or needs effectively. However, technology disruption resulting some problems among Indonesian children and teenagers, while qualified human resources are needed, human who are not only have competence in using technology, but also have competence in applying Islamic values that can strengthen their characters. This study uses a qualitative method, a library research. The writer collects and analyzes various, relevant and credible data related to this study. The results of the study indicates that the are some problems encountered by children and teenagers caused by digital technology such as juvenile delinquency and growth and development barriers of children. To solve children and teenagers problems in the era of society 5.0 Indonesian system of education have to refers to Islamic education. Islamic education applies from preschool level. Many types of Islamic education or knowledge to teach are tauhid, muroqabalah, ibadah, akhlak, adab, seerah, and basic of qur’anic. Basic aqidah refers to children faith, about rukun iman, ibadah refers to worship practice, rukun Islam, seerah refers to Prophet Muhammad SAW history, Akhlak refers to prophet Muhammad PbuH characters, such as patience, thoughtful, hardworking, wisdom and trustful. Qur’anic refers to qur’anic language, Arabic and memorizing juz Amma programs, all knowledge mentioned before designed in preschool learners curriculum breaks into daily program, monthly programs, and yearly programs. All of learning activities presented by teachers and preschool learners at school involve Islamic Education. Types of learning activities are: praying, every time before children beginning doing their project, share things with friends, work in group, reciting Hamdalah whenever they finish their project.